PEMBINAAN KARAKTER TANGGUNG JAWAB SANTRI MELALUI BUDAYA ORGANISASI PELAJAR ORPPENDA - Ahmad Lubadhul Fikri Ar Rifai; Musnur Hery; Abu Mansur (PAI RAFAH, 2019)
This study examines the character building of students' responsibility through the organizational culture of ORPPENDA students in Pondok Modern Daarul Abroor Banyuasin. The background problem of this research is the fact that there are some members of the organization who are less committed to carrying out the mandate, which should set an example to the “santri” and vice versa because they feel arrogant or pretentious to have authority. The main problem arises because of the lack of participation, communication and coordination between members of the organization's management in following the activities in the cottage. This research is a type of qualitative research. Data collection techniques used were observation, interviews and documentation. While the qualitative descriptive data analysis technique uses three steps namely data reduction, data presentation and drawing conclusions. The results of this study indicate that with their culture in organization their character of responsibility becomes better. In these organizations they embrace one another like family. In the process of fostering the character of santri responsibility through several stages of understanding; train; guide; example; getting used to; and provide penalties for students who violate and provide prizes for exemplary and outstanding students. While the cultural elements include the values, norms, and climate of the organization written in Teng Komando (TENGKO) which is an outline of the rules that exist in the modern daarul abroor huts as well as the daily, weekly, monthly and yearly routine activities that have become their habits. Through this culture the character of the students' responsibility is truly fostered and directed as the goal of the organization of student organizations is to support discipline and train the leadership of students as provisions when they are involved in society.